Elites in an Egalitarian Society Support for the Nordic Model - Gulbrandsen, Trygve (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Based on two unique survey studies of elites in Norway, this book examines whether elite attitudes towards central national issues have changed in the wake of international and national events and developments since 2000. The chapters examine elite integration and relations between elites and citizens in Norway as a means to discuss the continued viability of the Nordic welfare state model. This insight into how elites relate to central issues in Norwegian society and how they look upon citizens' political interest and competence in general, will be of interest to academics within sociology and political science, as well as journalists and commentators and policy makers.